Design Computing and Cognition 20 - Gero, John S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The papers in this volume are from the Ninth International Conference on Design Computing and Cognition (DCC 20) held virtually at the Georgia Institute of Technology, Atlanta, USA. They represent the state-of-the-art of research and development in design computing and design cognition including the increasingly active area of design cognitive neuroscience. They are of particular interest to design researchers, developers and users of advanced computation in designing as well as to design educators. This volume contains knowledge about the cognitive behavior of designers, which is valuable for those who need to gain a better understanding of designing.
Keywords: Engineering design; Artificial intelligence; Cognitive psychology; Engineering Design; Artificial Intelligence; Cognitive Psychology; Engineering design -- Data processing -- Congresses; Architectural design -- Data processing -- Congresses; Cognition -- Congresses; Computer-aided design -- Congresses